EVALUASI KEEFEKTIFAN SISTEM PENGENDALIAN INTERNAL PADA BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL KOTA SALATIGA - , LARAS INDAH F. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to gain an understanding of an adequate design of internal control systems and the effectiveness of internal control systems function in Badan Pelayanan Perizinan Terpadu dan Penanaman Modal Kota Salatiga. The type of this research is a qualitative descriptive with case study approach.The data collection techniques used in this research is to conduct in-depth interviews based on the Internal Control questionairre (ICQ) according to Appendices List Test on Peraturan Pemerintah Nomor 60 Tahun 2008 regarding the Government Internal Control System, and then supplemented by data on the observation and documentation. The conclusion of this research is the design of the internal control system for control environment and risk assessment elements are inadequate, and only function of internal control system of risk assessment element is not effective.